Strategi Public Relations Dalam Menangani Pemberitaan Negatif Di Media Massa Atas Pengoperasian Teknologi Pionir Indonesia - Toha, Muhammad; Anoh, Erman; Iswadi (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2023)
The purpose of this study was to determine the public relations strategy in dealing with negative coverage in the mass media on the operation of Indonesian pioneer technology. The method used in this study is a qualitative research method. The type of research used is a case study, with data collection methods of interviews, observation, and documentation. The results of the research conducted found that in dealing with negative issues, PT Halmahera Persada Lygend implemented several PR strategies that included transparency, open communication, and building good relations with the media and stakeholders. In addition, they are always willing to convey clear and accurate information, supported by a PR team trained in strategic use of social media and dealing with crisis communications effectively. By implementing these steps, companies have managed to maintain their image, ward off negative issues, and build a strong reputation. Keyword: Public Relations, Negative News, Mass Media